El Niño event declared: Impacts on the Limpopo river basin in Southern Africa expected - International Water Management Institute; International Maize and Wheat Improvement Center (International Water Management Institute, 2023)
A blog call on policymakers and research-for-development organizations to take action to mitigate the possible impacts of the current developing El Niño event on small-scale farmers and rural communities and to keep tracking seasonal climate fluctuations. Multiple climate prediction centers have concurred that this El Niño event will reach a “strong” category in the Northern Hemisphere by the winter of 2023-24.